Formal Reasoning of Various Categories of Widely Exploited Security Vulnerabilities Using Pointer Taintedness Semantics - Chen, Shuo; Pattabiraman, Karthik; Kalbarczyk, Zbigniew; Iyer, Ravishankar K. (Proceedings of IFIP International Information Security Conference, 2004)
This paper is motivated by a low level analysis of various categories of severe security vulnerabilities, which indicates that a common characteristic of many classes of vulnerabilities is pointer taintedness. A pointer is said to be tainted if a user input can directly or indirectly be used as a pointer value. In order to reason about pointer taintedness, a memory model is needed. The main contribution of this paper is the formal definition of a memory model using equational logic, which is used to reason about pointer taintedness. The reasoning is applied to several library functions to extract security preconditions, which must be satisfied to eliminate the possibility of pointer taintedness. The results show that pointer taintedness analysis can expose different classes of security vulnerabilities, such as format string, heap corruption and buffer overflow vulnerabilities, leading us to believe that pointer taintedness provides a unifying perspective for reasoning about security vulnerabilities.
Toulouse, France